2018
DOI: 10.2217/imt-2018-0006
|View full text |Cite
|
Sign up to set email alerts
|

Dual Role of Macrophage in Tumor Immunity

Abstract: Macrophages are significant in immune responses, assuming a defensive role. In contrast, macrophages often cause undesirable changes. These reactions are processes by which macrophages express different functional programs in response to microenvironmental signals, defined as M1/M2 polarization. Tumor immunity has been acknowledged for contributing to the elucidation of the mechanism and clinical application in cancer therapy. One of the mechanisms for the refractoriness to cancer immunotherapy is the producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
97
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 120 publications
(98 citation statements)
references
References 75 publications
1
97
0
Order By: Relevance
“…Within the tumor, macrophages are a major stromal component, in which they are commonly termed TAM, which exhibit functions similar to M2 macrophages and can be characterized as the M2d subtype . Among tumor‐infiltrating cells in some cancers, macrophages represent the largest population of cells, contributing to at least one‐third of the total tumor mass .…”
Section: M2b Macrophages and Diseasesmentioning
confidence: 99%
See 3 more Smart Citations
“…Within the tumor, macrophages are a major stromal component, in which they are commonly termed TAM, which exhibit functions similar to M2 macrophages and can be characterized as the M2d subtype . Among tumor‐infiltrating cells in some cancers, macrophages represent the largest population of cells, contributing to at least one‐third of the total tumor mass .…”
Section: M2b Macrophages and Diseasesmentioning
confidence: 99%
“…Among tumor‐infiltrating cells in some cancers, macrophages represent the largest population of cells, contributing to at least one‐third of the total tumor mass . Mounting evidences have shown that M2d macrophages can release some factors that directly stimulate tumor cell survival, proliferation, motility, and angiogenesis, and affect the tumor microenvironment via paracrine cytokines, leading to tumor metastasis and invasion …”
Section: M2b Macrophages and Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, M2 produces various anti-inflammatory factors that not only inhibit the immune system but also promote tumour angiogenesis, proliferation, invasion, metastasis and anti-apoptosis. As the major macrophage subtype in the tumour foci, M2 macrophages are involved in all aspects of tumour development and are also called tumour-associated macrophages (TAMs) [5,10,11].…”
Section: Introductionmentioning
confidence: 99%